Darut Tauhid: Modernizing a Pesantren Tradition - Zaki Nur'aeni (Studia Islamika, 2005)
This study presents a case study of the Daarut Tauhiid Pesantren in Bandung, West Java, which represents an emerging trend in recent years in Indonesia, that is, the growing popularity of what we refer to here as the 'virtual pesantren'. Employing such a term in relation to the pesantren tradition - a tradition that has existed in Indonesia for many centuries - palpably indicates the changing nature of the tradition.DOI: 10.15408/sdi.v12i3.583